HeartMate II Left Ventricular Assist Device Geometry on Chest Radiograph Does Not Correlate with Risk of Pump Thrombosis. Issue 2 (March 2016) - Han, Jason J.; Gaffey, Ann C.; Sooppan, Renganaden; Hung, George; Venkataraman, Chantel; Phillips, Emily; Howard, Jessica; McLean, Rhondalyn; Acker, Michael A.; Atluri, Pavan
Abstract : Pump thrombosis (PT) is a common and potentially life-threatening complication among HeartMate II (HMII; Thoratec, Pleasanton, CA) patients. There have been efforts to correlate HMII geometry with higher risk of PT. The aim of this study was to test the validity of using HMII inflow cannula angle (ICA) and pump pocket depth (PPD) to predict PT. We performed a retrospective analysis of patients implanted with HMII left ventricular assist devices (LVADs) from January 2011 to March 2014 at our institution. Three blinded reviewers measured ICA and PPD from chest x-rays at postimplantation and most recent follow-up time points. The diagnosis of PT was visually confirmed upon device explantation by benchtop evaluation. HeartMate II was implanted in 90 patients. Sixteen (20%) patients experienced PT. There was no statistical difference between PT and non-PT patients in their initial ICAs (56.0° ± 10.1 vs. 54.6° ± 10.8, p = 0.63) and PPD (86.7 ± 24.9 mm vs. 81.1 ± 32.2 mm, p = 0.46). Prediction of PT using ICA and PPD by receiving operating characteristic was negative (area under curve (AUC) = 0.54 and 0.55, respectively). Changes in HMII geometry were measured over 112.5 (interquartile range = 34.3–337.3) days. A decrease in PPD was observed ( p = 0.0001). Initial ICA was a significant predictor of future angle change and suggested a convergence toward the mean (55.4°) (analysis of variance p = 0.002). Pump thrombosis recurred in four (25%) patients. Postoperative ICA and PPD do not appear to predict PT in HMII patients in our experience. HeartMate II geometry changes over time secondary to remodeling with a decrease in PPD and a convergence toward the median in ICAs. Further investigation into the role of geometric ventricular assist device conformation postimplant may be warranted.